Effect of Density on Consolidation and Creep Parameters of Clay - Alhaji, Mustapha Mohammed; Alhassan, Musa; Adejumo, Taiye Waheed; Jibrin, Ramatu (Universitas Pendidikan Indonesia, 2020)
Effect of density on consolidation and creep parameters of a clay soil was investigated using a soil classified according to Unified Soil Classification System (USCS) as Clay of High plasticity (CH) and composing majorly of secondary minerals, including montmorillonite. The air-dried soil was compacted at five different compaction energy levels (Reduced Standard Proctor compaction energy, Standard Proctor compaction energy, West African compaction energy, Reduced Modified Proctor compaction energy, and Modified Proctor compaction energy). Specimens for consolidation tests were molded at the five different compaction energy levels (densities). The consolidation parameters (initial void ratio, compression index, and preconsolidation pressure) were observed to be empirically related to the compaction energy. The creep parameters (i.e. primary compression index, secondary compression index, and magnitude of creep) were observed to increase with increases in loading to 387kN/m2, after which the values decreased. Curves resulting from these relationships were observed to increase with increases in compaction energy level and tent towards straight line at Modified Proctor compaction energy. Maximum magnitude of creep estimated for three years was observed to reduce from 455.5 mm at Reduced Standard Proctor compaction energy through 268 mm at West African compaction energy to 247.4 mm at Modified Proctor compaction energy levels.